Identification of new genes regulating nodule development in Medicago truncatula: an in-silico approach - Mahboobeh Azarakhsh; Sara Eslami; Maryam Moghadas; Zahra Ataei (Journal of Genetic Resources)
Biological nitrogen fixation is a process by which atmospheric nitrogen could be converted to the bioavailable nitrogen forms for plants. Among plants, legumes have the ability to fix nitrogen through symbiotic interaction with a specific group of bacteria called rhizobia. Because of this interaction, organs named nodules form on the plant roots. Nodule organogenesis on plant roots begins with the perception of Nod factor by plant root cells. Downstream of Nod factor perception, activation of transcription factor (TF) signaling cascade in root tissue take place. This results in the formation of structure named infection thread and initiation of cell division in root cortex and finally formation of functional nodules. Due to the importance of biological nitrogen fixation to improve soil fertility, the molecular mechanism of nodule development is studied extensively. Here in order to identify new possible regulators that affect the formation of nodules during symbiosis in Medicago truncatula, the most significant symbiotic related TFs including MtIPD3, MtNSP1, MtNSP2, MtNIN, MtERN1, MtERN2, and MtERN3 were studied. Analyzing co-expressed genes with Phytozome database and examining interaction networks with STRING database have indicated potential new regulators involved in nodule development. According to our data, there is a high physical interaction score between IPD3 with some splicing factors and cell cycle proteins. This shows that IPD3 through interaction with these proteins could be involved in regulation of gene expression and cell cycle. Besides, we found a possible cytokinin transport gene ABCG38 and showed the activation of its expression in nodules compared to root. Moreover, we showed that auxin response factor Medtr2g043250 could be direct target of NIN transcription factor. Our results on potential regulators of nodule organogenesis will pave the way for additional researches.